Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy outcomes in peritoneal carcinomatosis: 11-year tertiary-center experience - Burak Dinçer; Ali Fuat Kaan Gök; Mehmet İlhan; Leman Damla Ercan; Cemil Burak Kulle; Celal Caner Ercan; Neslihan Berker; Cemalettin Ertekin (BMC Cancer)
Abstract Background Cytoreductive Surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) are techniques developed for curative treatment of peritoneal carcinomatosis (PC). Studies have shown that CRS + HIPEC provides a survival advantage in PC, and long-term survival can be achieved in selected cases. This study aimed to evaluate CRS + HIPEC cases performed for curative purposes and to examine the prognostic factors. Methods PC patients who underwent CRS + HIPEC with curative intent between January 2011 and September 2022 were included. Demographic, clinical, and pathological findings, procedure-specific parameters, complications, mortality, progression-free survival (PFS), and overall survival (OS) were analyzed. Results Optimal cytoreduction was achieved in 70% of the patients. The median PFS for the entire series was 9.2 months, while the median OS was 20.5 months, with a 3-year OS rate of 36%. Appendiceal origin, cytoreduction score, absence of lymph node metastasis, and absence of complications were factors associated with a positive impact on both PFS and OS. In multivariate analysis, cytoreduction score emerged as the sole independent factor influencing both PFS and OS. Conclusions Considering the results in our series, cases of PC in which complete cytoreduction can be achieved should be evaluated for CRS + HIPEC.